Accelerating Dataset Distillation via Model Augmentation - Zhang, Lei; Zhang, Jie; Lei, Bowen; Mukherjee, Subhabrata (Subho); Pan, Xiang; Zhao, Bo; Ding, Caiwen; Li, Yao; Xu, Dongkuan (2023 Computer Vision and Pattern Recognition, 2023)
Dataset Distillation (DD), a newly emerging field, aims at generating much smaller but efficient synthetic training datasets from large ones. Existing DD methods based on gradient matching achieve leading performance; however, they are extremely computationally intensive as they require continuously optimizing a dataset among thousands of randomly initialized models. In this paper, we assume that training the synthetic data with diverse models leads to better generalization performance. Thus we propose two model augmentation techniques, i.e. using early-stage models and parameter perturbation to learn an informative synthetic set with significantly reduced training cost. Extensive experiments demonstrate that our method achieves up to 20× speedup and comparable performance on par with state-of-the-art methods.
Highlight paper (2.5%)